Problems in FAIRifying Medical Datasets. - Lobe, M.; Matthies, F.; Staubert, S.; Meineke, F. A.; Winter, A. (Stud Health Technol Inform, 2020)
Despite their young age, the FAIR principles are recognised as important guidelines for research data management. Their generic design, however, leaves much room for interpretation in domain-specific application. Based on practical experience in the operation of a data repository, this article addresses problems in FAIR provisioning of medical data for research purposes in the use case of the Leipzig Health Atlas project and shows necessary future developments.
Keywords: *Databases, Factual